THE PRACTICE OF MERARIQ (RELATED MARRIAGE) IN THE SASAK TRIBE, REVIEWED FROM A HUMAN RIGHTS PERSPECTIVE - Berliana Febia Bahtiar Motulo; Muh. Jufri Ahmad (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the human rights foundation as a perspective for examining the practice of merariq (elopement) within the Sasak indigenous community. Merariq is a marital tradition where the prospective groom